2015
DOI: 10.1007/s11356-014-4014-1
|View full text |Cite|
|
Sign up to set email alerts
|

Acetylcholinesterase in zebrafish embryos as a tool to identify neurotoxic effects in sediments

Abstract: In order to clarify the suitability of zebrafish (Danio rerio) embryos for the detection of neurotoxic compounds, the acetylcholinesterase assay was adapted and validated with a series of priority pollutants listed as relevant for the European water policy (Aroclor 1254, 2,3-benzofuran, bisphenol A, chlorpyrifos, paraoxon-methyl, quinoline, and methyl mercury chloride) as well as acetonic extracts from three sediments of known contamination. The acute toxicities of the model substances and the sediment extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 67 publications
1
18
0
Order By: Relevance
“…Designed to suppress the abundance of selected organisms, pesticides inhibiting AChE are usually also toxic for non-targeted species (Bocquené and Galgani, 1998). Furthermore, it has been recently shown that other type of compounds, such as polychlorinated biphenyls or polycyclic aromatic hydrocarbon (PAHs), can inhibit AChE in environmental samples (Kang and Fang, 1997;Kais et al, 2015). This assay was chosen for the development of a new EDA procedure because of the effects AChE inhibitors can have on organisms such as fish and seabirds (Bocquené and Galgani, 1998;Oropesa et al, 2007) and furthermore because apart from selected pesticides (such as organophosphates and carbamates), only a few classes of compounds have been previously tested.…”
Section: Biological Tools For Effect-directed Analysismentioning
confidence: 99%
“…Designed to suppress the abundance of selected organisms, pesticides inhibiting AChE are usually also toxic for non-targeted species (Bocquené and Galgani, 1998). Furthermore, it has been recently shown that other type of compounds, such as polychlorinated biphenyls or polycyclic aromatic hydrocarbon (PAHs), can inhibit AChE in environmental samples (Kang and Fang, 1997;Kais et al, 2015). This assay was chosen for the development of a new EDA procedure because of the effects AChE inhibitors can have on organisms such as fish and seabirds (Bocquené and Galgani, 1998;Oropesa et al, 2007) and furthermore because apart from selected pesticides (such as organophosphates and carbamates), only a few classes of compounds have been previously tested.…”
Section: Biological Tools For Effect-directed Analysismentioning
confidence: 99%
“…AChE is responsible for the enzymatic degradation of acetylcholine (ACh), and its absence or low activity causes high levels of systemic ACh, which acts as a neurotransmitter [32]. Herein, we observed an increase in AChE activity, which is in general associated to neurotoxicity [33]; however, the literature also suggests that AChE may display antitumor activity, in addition to correlating tumor malignancy with low activity of AChE [34][35][36]. GSTs are vital in the Phase II detoxification enzymes pathway in humans, and they provide protection against toxins by catalyzing toxin conjugation with Glutathione (GSH) or passively binding to various exogenous/endogenous toxic molecules, including environmental toxins, carcinogens, chemotherapeutic agents, and products of oxidative stress [37,38].…”
Section: Discussionmentioning
confidence: 77%
“…Within the DanTox project (funded by the German Federal Ministry of Education and Research, BMBF from 2010 to 2013), existing assays could be developed further (Garcia-Käufer et al 2015, Hafner et al 2015), and novel mechanism-specific contact assays were introduced for a comprehensive assessment of the bioavailable toxicity in sediments Keiter et al 2010;Kais et al 2015;Schiwy et al 2015). New and valuable knowledge concerning the application of such bioassays and the underlying cellular mechanisms have been gained.…”
Section: Responsible Editor: Philippe Garriguesmentioning
confidence: 99%